N-demethyl-sauroxine, a novel Lycodine Group alkaloid from Huperzia saururus - Vallejo, Mariana Guadalupe (2013)
The present study describes the isolation and identification of N-demethyl-sauroxine, a novel Lycopodium alkaloid obtained from Huperzia saururus (Lam.) Trevis. (Lycopodiaceae). Its structure and relative stereochemistry were elucidated on the basis of its spectral data and chemical correlations. Additionally, acetylcholinesterase inhibitory activity was evaluated (IC50 = 209.6 ± 1.1 lM). The structure of the already identified alkaloid sauroxine was also re-validated through two dimensional NMR data.